Hubungan Stadium Kanker dan Jenis Terapi yang diberikan Dengan Tingkat Kualitas Hidup Penderita Kanker Buli-Buli di RSUP Dr. M. Djamil Padang Tahun 2018–2021 - Fikri Fadhil; Alvarino Alvarino; Gardenia Akhyar (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Quality of life is very important assessment in evaluating a person’s perception of the disease they have. Cancer stage characteristics and the type of therapy given to baldder cancer patients can affect the overall quality of life. This study aims to see the relationship of the stage of cancer and the type of therapy given with the quality of life. The type of this research is an analytical study with a cross sectional design. Sampling was done by consecutive sampling technique. The research took place from August 2021–March 2022 at RSUP Dr. M. Djamil Padang with a total sample of 64 people. The research instrument used was the EORTC QLQ-C30 questionnaire and medical records of patients with bladder cancer. Bladder cancer most often occurs in people with the age of >45 years old and male sex. The most found stage in bladder cancer is stage II and the most frequently implemented therapy is TURBT. Cancer stage and the type of therapy used had a statistically significant relationship with the quality of life of bladder people with the age of >45 years old and male sex. The most found stage in bladder cancer is stage II and the most frequently implemented therapy is TURBT. Cancer stage and the type of therapy used had a statistically significant relationship with the quality of life of bladder cancer patients (p=0.01; p=0.04). There is a significant relationship of the cancer stage and type of therapy given with the quality of life of bladder cancer patients.